Gestión ambiental con base en la NTP-ISO 14001:2002 para agroindustrias Dane S.R.L. en el distrito de la Banda de Shilcayo – San Martín - Navarro Ramírez, Enrique (2010)
The present research work “Environmental Management on the basis of the NTPISO 14001:2002 for Agroindustrias DANE S.R.L. at the district of the Banda de Shilcayo – San Martín”, you developed with the purpose to make an Environmental Management Manual for the milk processing plant of the mentioned company; it was proceeded to accomplishing an environmental initial diagnosis at the company with the purpose to identify all of emissions and waste matter, as well as his sources and costs of treatment and disposition for it. Besides information on consumption of water, characterization of effluents, esteem of losses, consumption of electric power, as well as the levels of manufactured noises were compiled. With all this information and right after applying an opinion poll on the basis of the standard's quantitative check list ISO 14001:2002; it was determined than Agroindustrias DANE S.R.L. only did his job with 6,34 % of this list, which is why it is concluded that he does not find an indication of the existence an Environmental Management System. With these findings, and with the application of a womb of priorities and assessment of environmental aspects, and diagram of Pareto, they determined the significant criteria and the environmental significant aspects. For the identification of these environmental aspects, a mapping of the processes of the milk plant came true besides; next with these results elaborating procedures, environmental policy, objectives, goals and elaborating an environmental management programme, which finalized with the design and obtaining of the Environmental Management Manual of Agroindustrias DANE S.R.L.